Osteosynthetic Materials Used in Open Reduction and Internal Fixation of Facial Fractures in University Hospital Setting- A Retrospective Study - M.Ashwin Shravan Kumar1 , Madhulaxmi Marimuthu2 , Revathi Duraisamy3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Facial fractures and management form a significant quantum of work for maxillofacial surgeons.Understanding the appropriate surgical techniques and materials can avoid complications like infections,implant loosening, improper healing and resurgeries. The aim of the study is to compare the two mostcommonly used osteosynthetic materials for open reduction and internal fixation - stainless steel and titanium.A retrospective data collection was done from March 2019 to June 2020 for a period of 10 months. Caserecords of patients who reported with facial trauma and underwent open reduction internal fixation(ORIF)were reviewed. There were 105 patients who reported with facial trauma, among which 47 patients neededORIF. Parameters analysed were age, gender, site of fracture and choice of plate material. Among these,44 were males and 3 were females. 35 patients were below 35 years and 12 patients were above 35 years.65% were treated using Titanium plate & 35 % with stainless steel plate. Chi square test was performed tostudy the statistical significance and p value was found to be (0.030)<0.05, statistically significant provingtitanium is more used in patients below 35 years of age.This study showed that titanium plates were mostcommonly preferred over stainless steel plates. This is in consensus with existing literature that titaniumplates are widely used for ORIF in facial fractures. However, though 35% of our study group still preferredto be treated with stainless steel plates. Whether age or socioeconomic reasons played a role in the choice oftreatment needs to be further evaluated with larger sample size and multicentre studies among our population.